The Beneficial Effects of Fiber on Major Chronic Diseases: A Review of Evidence - Fahime Zeinali; Mehnoosh Samadi; Niloofar Hojjati (Journal of Nutrition and Food Security, 2018)
Background: Fiber is a carbohydrate, which is neither completely digested nor absorbed in the small intestine, but may be fermented and plays a key role in the human health. We investigated the beneficial effects of fiber on major chronic diseases. Methods: It was extracted the relevant articles by searching the PubMed, ScienceDirect, and Scopus databases using the following keywords: dietary fiber, carbohydrate fermentation, short chain fatty acids, cardiovascular disease, diabetes, cancer, constipation, and appetite. In this research, a variety of studies were investigated including prospective cohort, case-control, cross-sectional, and clinical trial. The thematic relation of these studies was evaluated by reviewing their titles and abstracts. Results: From a total of 123 articles, 27 related studies with appropriate design and reliable information were selected and reviewed. Considering the selected studies, 13 were clinical trials, 10 articles were cohort, one was case-control, and three studies were cross-sectional. The studies investigated the beneficial effects of fiber on cardiovascular diseases (N = 4), type 2 diabetes (N = 8), appetite control and body weight (N = 3), colorectal cancer (N = 4), breast cancer (N = 2), immune system (N = 3), and constipation (N = 3). According to the results of this study, fiber reduces the rate of gastrointestinal discharges; this in turn leads to decrease of the glucose uptake and increases the satiety. More fiber consumption was associated with improvement of the immune system, weight control, reduction of the cardiovascular diseases, diabetes, colon cancer, and breast cancer. Conclusions: Regular consumption of fiber has beneficial health outcomes. However, these benefits depend largely on the types of the consumed fiber and the individual who intakes them.